Schwann cell reprogramming via EMT-like program following peripheral nerve injury and during nerve regeneration - Dai, Wenyu; Miao, Yang; Yi, Sheng (Frontiers in Cell and Developmental Biology, 2025)
The activation of the epithelial-mesenchymal transition (EMT) enhances cell plasticity and plays a pivotal role in driving critical biological processes such as embryonic process, tissue repair, and cancer metastasis. EMT is regulated by multiple signaling pathways, including transforming growth factor-β (TGF-β), Wnt, and Notch signaling, and is finely orchestrated by a network of transcriptional factors, epigenetic modifications (such as DNA methylation and histone alterations), and non-coding RNAs. In the peripheral nervous system, Schwann cells undergo a distinct EMT-like transformation following nerve injury, adopting a repair phenotype known as repair Schwann cells. These repair Schwann cells play a multifaceted role in nerve regeneration by clearing myelin debris, secreting regeneration-promoting factors, mediating structural reorganization, and creating a conducive microenvironment for axonal regrowth. Therapeutic strategies targeting the regulation of the EMT-like program of Schwann cells thus hold significant promise for the treatment of peripheral nerve injury, particularly in cases of severe nerve injury with incomplete recovery and poor functional restoration.